Overview of the Level of Knowledge and Attitude of the Community about the Practice of Antihistamine Drug Self-Medication in Handling Allergies in Biawu Village, South Kota District - Nur Inzan Van Solang; Siti Rahma; Gusti Pandi Liputo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Self-medication of antihistamines for the treatment of allergies is a common practice in the community. However, a lack of understanding of dosage, indications, and side effects can pose health risks. This study aims to find out how the level of knowledge and public attitudes about the practice of self-medication of anthistamines in handling allergies in Biawu village, South Kota District. This research method uses a cross-sectional design with a quantitative descriptive approach. The sample totaled 97 respondents who were selected by purposive sampling. Data was collected using a structured questionnaire that has been tested for validity and reliability. Data analysis was carried out descriptively. The population of this study is all people in Biawu village, south Kota district. The results showed that the majority of respondents as many as 58.8% of respondents had a high level of knowledge, 15.5% moderate, and 25.8% low about antihistamine self-medication. Most respondents (96.9%) had a moderate attitude, and only 3.1% had a high attitude. In terms of practice, 62.9% of respondents had high self-medication practices, 27.8% moderate, and 9.3% low. As many as 83.5% of respondents often buy drugs without a medical prescription, and the main source of information is personal/family experience (66%). The conclusion of the study is that although the majority of the public has knowledge of the dangers high practice of antihistamine self-medication. However, the attitude and practice of self-medication is still in the high category. The need for sustainable health education and the active role of health workers in guiding the community to carry out rational and safe self-medication.